In vitro, in vivo and in silico metabolic profiling of α-pyrrolidinopentiothiophenone, a novel thiophene stimulant. (January 2016) - Swortwood, Madeleine J; Carlier, Jeremy; Ellefsen, Kayla N; Wohlfarth, Ariane; Diao, Xingxing; Concheiro-Guisan, Marta; Kronstrand, Robert; Huestis, Marilyn A
Background: Little or no pharmacological or toxicological data are available for novel psychoactive substances when they first emerge, making their identification and interpretation in biological matrices challenging.Materials & methods: A new synthetic cathinone, α-pyrrolidinopentiothiophenone (α-PVT), was incubated with hepatocytes and samples were analyzed using liquid chromatography coupled to a Q Exactive TM Orbitrap mass spectrometer. Authentic urine specimens from suspected α-PVT cases were also analyzed. Scans were data mined with Compound Discoverer™ for identification and structural elucidation of metabolites.Results/conclusion: Seven α-PVT metabolites were identified in hepatocyte incubations, and in the authentic urine samples, also with an additional monohydroxylated product and a glucuronide of low intensity. α-PVT dihydroxypyrrolidinyl, α-PVT 2-ketopyrrolidinyl, α-PVT hydroxythiophenyl and α-PVT thiophenol had the most intense in vivo signals.